KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN RECIPROCAL TEACHING DENGAN BERBANTUAN ALAT PERAGA â€œKARTU PINTARâ€ PADA MATERI PRISMA DAN LIMAS KELAS VIII SMP NEGERI 1 PANDAAN TAHUN AJARAN 2017/2018 - Putri Amalia Cahyani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2019)
The purpose of this study was to determine whether there is an increase in mathematical reasoning abilities and to describe the mathematical reasoning abilities of students through the Reciprocal Teaching learning model assisted with